Standard English Grammar and Professional Identity: Perceptions of EFL Students in Language Education - Setyawan, Sunoko; Pramudita, Rizqi Febrian; Astuti, Yuni (English Department, Universitas Negeri Surabaya, 2025)
The demand for formal English proficiency both in academic and professional environments highlights the critical role of Standard English Grammar in building effective communication and professional identity. This study investigates how EFL students in a university’s English Language Education Study Program perceive the importance of standard grammar in professional contexts. Employing a descriptive qualitative approach, data were collected from first-semester undergraduate EFL students (N=40) through a structured questionnaire and semi-structured interviews. The questionnaire combined Likert-scale items with open-ended questions, while the interviews provided deeper insights into students’ experiences and expectations regarding the teaching of grammar in their classroom. Findings show that the majority of students recognize standard grammar as essential for maintaining credibility and professionalism, especially in tasks such as academic writing, formal email correspondence, job interviews, and public speaking. However, a significant gap exists between students’ awareness of the importance of grammatical aspect and their ability to apply it effectively in real-world contexts. The analysis also identifies students’ concerns about the de-contextualized nature of grammar instruction and their preference for contextual, task-based learning approaches that simulate professional communication. The study underscores the need to align Grammar curricula with professional demands by embedding grammar instruction into authentic learning materials. These findings have implications for the development of EFL curriculum, emphasizing the integration of grammatical competence with professional literacy. By rethinking the grammar instruction through a contextualized lens, educators are expected to support students in constructing confident professional identities.